Redox-responsive and pH-sensitive nanoparticles enhanced stability and anticancer ability of erlotinib to treat lung cancer in vivo - Tan S; Wang G (Dove Medical Press, 2017)
Sheng Tan, Guoxiang Wang Department of Thoracic Surgery, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China Purpose: Erlotinib (ETB) is a well-established therapeutic for non-small-cell lung cancer (NSCLC). To overcome drug resistance and severe toxicities in the clinical application, redox-responsive and pH-sensitive nanoparticle drug delivery systems were designed for the encapsulation of ETB. Methods: Poly(acrylic acid)-cystamine-oleic acid (PAA-ss-OA) was synthesized. PAA-ss-OA-modified ETB-loaded lipid nanoparticles (PAA-ETB-NPs) were prepared using the emulsification and solvent evaporation method. The tumor inhibition efficacy of PAA-ETB-NPs was compared with that of ETB-loaded lipid nanoparticles (ETB-NPs) and free ETB anticancer drugs in tumor-bearing mice. Results: PAA-ETB-NPs had a size of 170 nm, with a zeta potential of -32 mV. The encapsulation efficiency and drug loading capacity of PAA-ETB-NPs were over 85% and 2.6%, respectively. In vitro cytotoxicity of ETB-NPs were higher than that of ETB solution. The cytotoxicity of PAA-ETB-NPs was the highest. The in vivo tumor growth inhibition by PAA-ETB-NP treatment was significantly higher than that by ETB-NPs and ETB solution. No obvious weight loss was observed in any of the treatment groups, indicating that all the treatments were well tolerated. Conclusion: PAA-ETB-NPs could enhance the stability and anti-cancer ability of ETB to treat lung cancer and are a promising drug delivery system for lung cancer treatment. Keywords: epidermal growth factor receptor, kinase inhibitor, pH-sensitive, redox-responsive, poly(acrylic acid)